Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.physleta.2010.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Can elemental bismuth be a liquid crystal?

Abstract: A number of anomalies have been reported in molten Bi, including a first-order liquid-liquid transition at 1010K and ambient pressure, which is irreversible at cooling rates of several degrees per minute. An interpretation of these effects as due to long-range orientational order is suggested. Significant evidence for directionality in liquid Bi, albeit only immediately after melting, is available in experiments made circa 1930. Further experimentation is called for.Comment: 10 pages, no figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Previous studies have suggested that this plateau is associated with a structural rearrangement in the liquid state. 20,24,25,26 We suggest that this phenomenology reflects a broad maximum in the sound velocity, analogous to that observed in liquid Sb and is typical to column V in the periodic table. To estimate the behavior of the sound velocity near the melting point, we have fitted the temperature dependence to a third-order polynomial (Fig.…”
Section: Liquid Pnictide Hypothesessupporting
confidence: 69%
“…Previous studies have suggested that this plateau is associated with a structural rearrangement in the liquid state. 20,24,25,26 We suggest that this phenomenology reflects a broad maximum in the sound velocity, analogous to that observed in liquid Sb and is typical to column V in the periodic table. To estimate the behavior of the sound velocity near the melting point, we have fitted the temperature dependence to a third-order polynomial (Fig.…”
Section: Liquid Pnictide Hypothesessupporting
confidence: 69%
“…Indeed, undercooled liquid L by droplet emulsion forms metastable crystals at ambient condition with structure that is distinct from that of Bi-I but similar to that of the monoclinic Bi-II phase (44). It is, therefore, likely that this peak represents a remnant of the bilayer-like units in liquid L, consistent with the two-step liquid model (41). The irreversible liquid structure change above ∼1,250 K at 2.0 GPa indicates that, around this pressure and at temperatures deep in the liquid state, Bi possesses certain "memory" of the L structural units on cooling.…”
Section: Discussionmentioning
confidence: 54%
“…S1). Based on the complex interatomic binding in rhombohedral Bi-I, the 1-atm melting process has been postulated to occur in two discrete steps (41). The first step involves loosening of the adjacent bilayers, leading to a liquid crystal-like (or "smecticlike") liquid (L) near 544 K, while retaining the threefold rotational symmetry in the Bi4 motifs in the bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…A particularly interesting question is the mechanism behind the LLPTs in bismuth. In fact, one of the present authors has speculated that the covalently-bonded bilayer sheets of crystalline bismuth become only partly disordered at melting (545 K), and fully disintegrate only at the LLPT at 1010 K. 59 This would mean that the phase obtained by melting of solid bismuth consists of 2D polymers (the bilayers), which are unable to pass through each other, but able to glide in the transverse directions, possibly becoming crumpled, thus adding to the disorder. This suggested mechanism also provides a reasonable context for explanation of the recently-observed anomalies of Refs.…”
Section: Summary and Discussionmentioning
confidence: 65%